Dose Distribution of 123I in the Thyroid Gland and its Maximum Permissible Concentrations - Pedroli, G.; Conte, L.; Silvani, R. (Nuklearmedizin - NuclearMedicine, 1976)
The calculation of the dose distribution in the thyroid tissues and of the maximum permissible concentrations in the air and in drinking water was carried out for 123I. In fact because of the recent use of this radionuclide in radioisotopic diagnostics the dose to both the patients’ and operators’ thyroids due to 123I must to be known.In order to obtain a correct estimate it is necessary, however, to consider the distribution of the radionuclide in the thyroid tissue and the changes in this distribution depending on the dimensions of the follicles. Taking into account the dose at the follicular cell-colloid interface, the maximum permissible concentrations in the air and in drinking water were calculated as being 6 x 10–8 μCi/cm3 and 4 x 10–4 μCi/cm3 respectively.